EVALUASI PENYIMPANAN OBAT DI INSTALASI FARMASI PUSKESMAS PERTIWI KOTA MAKASSAR TAHUN 2021 - Muhammad Tahir (Jurnal Kesehatan Yamasi Makassar, 2022)
This study was conducted in July 2021 with the aim of evaluating drug storage at the Pharmacy Installation of the Pertiwi Health Center Makassar. This research was conducted using direct observation method by matching (check list). The drug storage system implemented at the Pertiwi Health Center Makassar pharmacy has met the requirements according to the Minister of Health Regulation No. 74 of 2016 with an evaluation of good drug storage. The data is processed using the Guttman scale and the results of the study show that the drug storage system applied at the Pertiwi Makassar Health Center pharmacy in 2021 can be categorized as fulfilling because the score results show 81% according to the objective criteria.